Influence of Nano Nickel Oxide (NNO) Particles on Hydrogen Production in Dark Fermentation of Palm Oil Mill Effluent - Puranjan, Mishra; Singh, Lakhveer; Zularisam, A. W. (Universiti Malaysia Pahang, 2016)
Batch experiment with initial pH of 5.5, was conducted to produce hydrogen from palm oil mill effluent (POME). Nano nickel oxide (NNO) particles were supplemented (20-140 mgł) to POME to enhance biohydrogen production. Clostridium species LS2 was used as inoculum. At initial hydrogen production rate was significantly increased from 2 to 15 ml H2/h with the increasing NNO particle concentration from 20 to 80 mg/l.. While the NNO concentration continued to increase from 80 to 140 mg/l, the hydrogen production rate gradually decreased. The maximum COD removal potential of 59 % was obtained in the presence of 80 mg/l of NNO after 96 h of dark fermentation. Addition of nano micronutrient to the production medium enhanced the hydrogen production rate and COD removal efficiency thus improved concurrent hydrogen production and pollution reduction from POME with activated sludge.